Social exclusión. Theoretical discussion and case studies - Camacho Monge, Daniel (2023)
The concept “social exclusion” used excessively in social science is, at the same time, polysemic and imprecise. Various meanings are attributed to it, which most analysts attribute to the lack of clarity about its theoretical location. It is frequently claimed that it is not rooted in any theory. In addition, two broad currents can be identified in this regard. On the one hand, those that place in the field of social exclusion those conglomerates or individuals who are outside the prevailing economic and cultural system, dominant and promoter of the dynamics of society as capitalism would be at the present time and, on the other hand, those who conceive it as their necessary product.